A comprehensive investigation of guaiacyl-pyranoanthocyanin synthesis by one-/two-dimensional NMR and UPLC–DAD–ESI–MSn. (15th May 2016) - Vallverdú-Queralt, Anna; Meudec, Emmanuelle; Ferreira-Lima, Nayla; Sommerer, Nicolas; Dangles, Olivier; Cheynier, Véronique; Guernevé, Christine Le
Highlights: Formation of guaiacylpyranomalvidin 3- O -G was investigated by LC–DAD–MS and NMR. Conditions were optimized and reaction yields precisely determined by quantitative NMR. Major reaction products were identified by UPLC–DAD–MS and NMR. Malvidin 3- O -G degradation competed with guaiacylpyranomalvidin 3- O -G formation. At pH 1, vinylguaiacol polymers competed with vinylguaiacol for formation of pyranoanthocyanins. Abstract: In red and rosé wines, the grape anthocyanins are progressively converted to more stable pigments, including phenylpyranoanthocyanins. One-/two-dimensional NMR and UPLC–DAD–ESI–MS n measurements were used to monitor the synthesis of guaiacylpyranomalvidin 3- O -glucoside from malvidin 3- O -glucoside and vinylguaiacol in model solutions and identify the products formed during the reaction. The highest conversion rates (30%, determined by 1 H qNMR) were obtained with a small excess of vinylguaiacol in methanol/water (70/30) at pH 3 and 35 °C. Two reaction pathways competed with the formation of guaiacylpyranomalvidin 3- O -glucoside. The first one only concerns malvidin 3- O -glucoside and consists in C-ring cleavage with formation of malvone and smaller molecular weight breakdown products. This pathway is favored at higher pH and incubation temperature. At lower pH values or in the presence of large vinylguaiacol excess, faster consumption of malvidin 3- O -glucoside resulted from the formation of more complex pyranoanthocyanins substituted by vinylguaiacol oligomers.